Characterization of Vibrio parahaemolyticus isolated from coastal seawater in Peninsular Malaysia - Lesley Maurice, Bilung; Gwendelynne, Bulan Tanil; Nishibuchi, Mitsuaki; Son, Radu; Raha, Abdul Rahim; Suhaimi, Napis; Gunsalam, Jurin Wolmon (Central Coordinating Board for Tropical Medicine and public Health Project of SEAMEC, 2005)
Twenty-one Vibrio parahaemolyticus isolates representing 21 samples of coastal seawater from three beaches in peninsular Malaysia were found to be sensitive to streptomycin, norfloxacin and chloramphenicol. Resistance was observed to penicillin (100%), ampicillin (95.2%), carbenicilin (95.2%), erythromycin (95.2%), bacitracin (71.4%), cephalothin (28.6%), moxalactam (28.6%), kanamycin (19.1%), tetracycline (14.3%), nalidixic acid (9.5%) and gentamicin (9.5%). Plasmids of 2.6 to 35.8 mDa were detected among plasmid-containing isolates. All isolates carried the Vp-toxR gene specific to V. parahaemolyticus and were negative for the tdh gene, but only one isolate was positive for the trh gene. DNA fingerprinting of the isolates using ERIC-PCR and PFGE showed that the isolates belong to two major clonal groups, with several isolates from different locations in the same group, indicating the presence of similar strains in the different locations.